Design of a wireless sensor network for optimal deployment of sensor nodes in a cocoa crop (2020)
In this study, factorial experiments were conducted in two different scenarios to design a Wireless Sensor Network for monitoring a cocoa crop in a rural area in Colombia. Node sensors measured temperature, relative humidity, soil moisture, Ultra-Violet light, and visible light intensity. The factors considered in the experiments were distance between node sensors, height from the ground, and type of antenna; in turn, Received Signal Strength Indicator and data transfer time were the outputs. The wireless sensor network was deployed in the crop, covering approximately 3 % of the area and using 7 different nodes in a cluster tree topology. First, an open field scenario with line of sight was used to determine the appropriate height of the node sensors. Second, a scenario in the actual cocoa crop was utilized to find the appropriate distance between modules and type of antenna. We found, based on our calculations and experimental data, that a height of 1.25 m was required to avoid the Fresnel zone and improve the RSSI of the network. Furthermore, we determined that a distance below 35 m was needed to guarantee signal reception and avoid long data transfer times. The wire antenna exhibited a better performance. Finally, the proposed methodology and monitoring system can be used for agronomic applications in rural areas in Colombia to increase crop yield.